Delivering comprehensive HIV services across the HIV care continuum: a comparative analysis of survival and progress towards 90-90-90 in rural Malawi. Issue 1 (12th January 2018) - Wroe, Emily B; Dunbar, Elizabeth L; Kalanga, Noel; Dullie, Luckson; Kachimanga, Chiyembekezo; Mganga, Andrew; Herce, Michael; Beste, Jason; Rigodon, Jonas; Nazimera, Lawrence; McBain, Ryan K
Abstract : Introduction: Partners In Health and the Malawi Ministry of Health collaborate on comprehensive HIV services in Neno, Malawi, featuring community health workers, interventions addressing social determinants of health and health systems strengthening. We conducted an observational study to describe the HIV care continuum in Neno and to compare facility-level HIV outcomes against health facilities nationally. Methods: We compared facility-level outcomes in Neno (n=13) with all other districts (n=682) from 2013 to 2015 using mixed-effects linear regression modelling. We selected four outcomes that are practically useful and roughly mapped on to the 90-90-90 targets: facility-based HIV screenings relative to population, new antiretroviral therapy (ART)enrolments relative to population, 1-year survival rates and per cent retained in care at 1 year. Results: In 2013, the average number of HIV tests performed, as a per cent of the adult population, was 11.75%, while the average newly enrolled patients was 10.03%. Percent receiving testing increased by 4.23% over 3 years (P<0.001, 95% CI 2.98% to 5.49%), while percent enrolled did not change (P=0.28). These results did not differ between Neno and other districts (P=0.52), despite Neno having a higher proportion of expected patients enrolled. In 2013, the average ART 1-year survival was 80.41% nationally and 91.51% in Neno, which is 11.10% higher (P=0.002, 95% CI 4.13% to 18.07%). One-year survival declined by 1.75% from 2013 to 2015 (P<0.001, 95% CI −2.61% to −0.89%); this was similar in Neno (P=0.83). Facility-level 1-year retention was 85.43% nationally in 2013 (P<0.001, 95% CI 84.2% to 86.62%) and 12.07% higher at 97.50% in Neno (P=0.001, 95% CI 5.08% to19.05%). Retention declined by 2.92% (P<0.001, 95% CI −3.69% to −2.14%) between 2013 and 2015, both nationally and in Neno. Conclusion: The Neno HIV programme demonstrated significantly higher survival and retention rates compared with all other districts in Malawi. Incorporating community health workers, strengthening health systems and addressing social determinants of health within the HIV programme may help Malawi and other countries accelerate progress towards 90-90-90.